Real options and real value: The role of employee incentives to make specific knowledge investments - WANG, Heli (Institutional Knowledge at Singapore Management University, 2008)
Real options reasoning emphasizes the strategic value of making flexible investments in a turbulent environment. Employees' investments in specific human capital are often critical to the success of a real option project, but the very flexibility that allows a firm to change course in response to new information also affects employees' incentives to make such specific human capital investments. We develop a model of real option investment that explicitly incorporates the role of employee incentives. The model suggests that the effect of investing in a real option project on employee incentives may be positive, further increasing the value of the project, or negative, sometimes more than offsetting the benefit of flexibility and resulting in reduced project value. Therefore, firms and managers should take into consideration the role of employee incentives when applying real options logic to investment decision making.